Determinants of outpatient expenditure within primary care in the Brazilian National Health System: Determinantes de gastos ambulatoriais na atenção primária do sistema público de saúde brasileiro - Turi, Bruna Camilo; Codogno, Jamile Sanches; Sarti, Flávia Mori; Anokye, Nana Kwame; Fernandes, Rômulo Araújo; Monteiro, Henrique Luiz (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: One of the big challenges facing governments worldwide is the financing of healthcare systems. Thus, it is necessary to understand the factors and key components associated with healthcare expenditure. The aim here was to identify demographic, socioeconomic, lifestyle and clinical factors associated with direct healthcare expenditure within primary care, among adults attended through the Brazilian National Health System in the city of Bauru. DESIGN AND SETTING: Cross-sectional study conducted in five primary care units in Bauru (SP), Brazil. METHODS: Healthcare expenditure over the last 12 months was assessed through medical records of adults aged 50 years or more. Annual healthcare expenditure was assessed in terms of medication, laboratory tests, medical consultations and the total. Body mass index, waist circumference, hypertension, age, sex, physical activity and smoking were assessed through face-to-face interviews. RESULTS: The total healthcare expenditure for 963 participants of this survey was US 112,849.74 (46.9% consultations, 35.2% medication and 17.9% laboratory tests). Expenditure on medication was associated with overweight (odds ratio, OR = 1.80; 95% confidence interval, CI: 1.07-3.01), hypertension (OR = 3.04; 95% CI: 1.91-4.82) and moderate physical activity (OR = 0.56; 95% CI: 0.38-0.81). Expenditure on consultations was associated with hypertension (OR = 1.67; 95% CI: 1.12-2.47) and female sex (OR = 1.70; 95% CI: 1.14-2.55). CONCLUSIONS: Our results showed that overweight, lower levels of physical activity and hypertension were independent risk factors associated with higher healthcare expenditure within primary care.